2016
DOI: 10.1037/abn0000115
|View full text |Cite
|
Sign up to set email alerts
|

General and specific attention-deficit/hyperactivity disorder factors of children 4 to 6 years of age: An exploratory structural equation modeling approach to assessing symptom multidimensionality.

Abstract: We tested first-order factor and bifactor models of attention-deficit/hyperactivity disorder (ADHD) using confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM) to adequately summarize the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, (DSM-IV-TR) symptoms observed in a Spanish sample of preschoolers and kindergarteners. Six ESEM and CFA models were estimated based on teacher evaluations of the behavior of 638 children 4 to 6 years of age. An ESEM bifactor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 68 publications
5
42
0
1
Order By: Relevance
“…The inattention (IA) subscale total score had a mean of 15.15 (SD = 5.89), and the hyperactivity-impulsivity (HI) subscale total had a mean of 16.46 (SD = 6.40). As expected [ 30 ], a sex comparison revealed significant differences: Boys scored higher on symptomology for both the IA ( F (1, 782) = 11.69, p = 0.001) and HI ( F (1, 782) = 5.122, p = 0.024) scales.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The inattention (IA) subscale total score had a mean of 15.15 (SD = 5.89), and the hyperactivity-impulsivity (HI) subscale total had a mean of 16.46 (SD = 6.40). As expected [ 30 ], a sex comparison revealed significant differences: Boys scored higher on symptomology for both the IA ( F (1, 782) = 11.69, p = 0.001) and HI ( F (1, 782) = 5.122, p = 0.024) scales.…”
Section: Resultssupporting
confidence: 80%
“…To ensure that the calibrated scale is useful, IRT requires that the empirical data fit the theoretical model. Although we do not have a universally accepted and unambiguous goodness-of-fit test [ 11 , 30 ], we nevertheless offer some evidence, which according to the literature, suggests a good fit [ 46 ]. Thus, we examine how easy it is to reach convergence, the size of the standard errors, M 2 and RMSEA statistics, the standardized local dependence statistics of each couplet of items, and the invariance of the discrimination and localisation parameters in two randomly selected subsamples.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Bifactor models of ADHD and the disruptive behavior disorders have also been fit (Arias, Ponce, Martínez-Molina, Arias, & Núñez, 2016; Martel, Gremillion, Roberts, von Eye, & Nigg, 2010; Martel, Roberts, Gremillion, von Eye, & Nigg, 2011; Martel, von Eye, & Nigg, 2012; Martel, von Eye, & Nigg, 2010; Toplak et al, 2009; Toplak et al, 2012) and significant bivariate correlations have been reported between (a) performance on the stop signal reaction time task (a measure of inhibitory control) and Trails A/B (a broad measure of set shifting) and (b) latent factor scores for hyperactivity/impulsivity and a general ADHD (but not a specific inattention) factor (Martel et al, 2011). That being said, it’s not clear whether the associations between the specific hyperactivity factor and performance would have remained significant if the relationship to general ADHD had been simultaneously parceled, or if more robust/latent indices of executive control had been used.…”
Section: Resultsmentioning
confidence: 99%
“…In general, mea-surement invariance across groups deals with whether the observed scores on a measure are the same across the groups when these scores "represent" the same level (intensity, severity) of the underlying latent trait score. [18,19] Lack of support for invariance indicates that the scores obtained by the groups cannot be accurately compared on the measure used, since any difference could be confounded by discrepancies in the scaling properties of the measure for the groups. [20] When applied to ADHD rating scales, measurement invariance across groups of children with and without ADHD refers to observed ADHD scores being the same across these groups, when individuals in the groups have the same level of the underlying ADHD latent trait.…”
Section: Introductionmentioning
confidence: 99%